Case reports of two unusual breast lumps (Journal of Pathology of Nepal, 2013)
Breast lump is a common diagnostic problem both to the general practitioner and to the surgeons. Cases like mammary myxoma and cysticercosis are rare findings and their diagnosis needs to be confirmed on histopathology. Myxoma of the breast is extremely rare and presents with painless swelling. Cysticercosis can affect any organ or tissue of the body and involvement of the breast is unusual. We present reports on two unusual breast lumps in young females with mammary myxoma and cysticercosis. The clinical presentation and its histopathological diagnosis is discussed. Journal of Pathology of Nepal (2013) Vol. 3, No.1, Issue 5, 422-424 DOI: http://dx.doi.org/10.3126/jpn.v3i5.7874